(untitled) (Research, Society and Development, 2022)
Introduction: Alzheimer’s is a degenerative disease that presents in its predominance with elderly people, whose characteristics are memory loss, cognitive difficulties and inability to carry out activities as well as to make decisions, creating a total dependence on the family. Objective: The article in question aims to analyze the social representations of Alzheimer’s disease from the perspective of the family caregiver and as a specific objective to identify the causes of Alzheimer’s in the elderly; describe the experiences and feelings experienced by caregivers; cite the factors that influence the impact on family caregivers. Methodology: is based on a literature review of the integrative literature review type, collecting 7 academic articles that were available regarding the central theme. Result: The collected data understood the difficulty that the caregiver has in dealing with the patient’s diagnosis, having to deal with several impasses caused by the confirmation of the disease, both emotional and physical, as well as beliefs and non-acceptance by family members. Conclusion: It is concluded that the overloaded caregiver tends to have reactions that can cause stress, feelings of guilt and loss of patience, which causes a very strong emotional strain, bringing with it a difficulty in dealing with the elderly who are not at fault. none of them are in that situation, and there must be a family support network for both the elderly and the caregiver.